Barzanji Reading Traditions in Schools - Nurhayati, Fitri; Hanafi, Hanafi; Rochman, Boy Arief (STAI AL-FALAH CICALENGKA, 2021)
Discipline has always been something that many people talk about, be it discipline in the family, community or school. Especially discipline in an educational institution, because discipline is very influential on the success of teachers in educating their students. Discipline also requires support and encouragement in order to survive, something that can make discipline run well is the existence of disciplinary tools. One of them is punishment, punishment is intended to change or improve behavior, after the student realizes and regrets the wrong he has done. This study aims to answer the problems: How is the effectiveness of reading Barzanji on discipline at SMK Ganesha Parakan Muncang and How is the impact of reading Barzanji on student learning at SMK Ganesha. This research uses qualitative methods and is a field research using a research study approach. The method used is descriptive research. The subjects of this research are the School Founder, Principal, Student Affairs teachers, teachers and students. Data collection techniques through observation, interviews, and documentation. The results of the study indicate that the policies implemented by the school in instilling discipline include rules of conduct, consistency and punishment. Based on observations and interviews, it is clear that there is a change from before and after the Barzanji reading. Barzanji readings are carried out according to a structured schedule. This condition cannot be separated from the commitment of every teacher in charge of disciplining students. The results of the study can be concluded that the effectiveness of reading Barzanji on the discipline of Ganesha Vocational School students is for time discipline, learning discipline and discipline in attitude. Not only that, because students read Barzanji every day as an inner recitation to cultivate the characteristics of children to become religious, emotional and spiritual students. When entering the class students become calm, relaxed and cool individuals. In contrast to the students before the Barzanji reading was held, when entering the class and then waiting for the bell to ring, the students joked a lot with their friends which resulted in chaos in the class. Keywords: Barzanji Reading, Student Discipline Abstrak Kedisiplinan selalu menjadi hal yang banyak dibicarakan orang, baik itu disiplin dalam keluarga, masyarakat maupun sekolah. Terutama disiplin dalam suatu lembaga pendidikan, sebab kedisiplinan sangat berpengaruh terhadap keberhasilan guru dalam mendidik siswanya. Kedisiplinan juga membutuhkan dukungan dan dorongan agar bisa tetap bertahan, sesuatu yang bisa menjadikan kedisiplinan berjalan dengan baik yaitu adanya alat kedisiplinan. Salah satunya adalah hukuman, hukuman ditujukan untuk merubah atau memperbaiki tingkah laku, setelah siswa menyadari dan menyesali perbuatan salah yang telah dilakukannya. Penelitian ini bertujuan untuk menjawab permasalahan: Bagaimana keefektifan pembacaan Barzanji terhadap kedisiplinan di SMK Ganesha Parakan Muncang dan Bagaimana dampak pembacaan Barzanji dalam pembelajaran siswa di SMK Ganesha. Penelitian ini menggunakan metode kualitatif dan merupakan penelitian lapangan (field research) dengan menggunakan pendekatan studi penelitian. Metode yang digunakan adalah penelitian deskriptif. Subyek penelitian ini adalah Pendiri Sekolah, Kepala Sekolah, guru Bidang Kesiswaan, guru-guru dan siswa. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa kebijakan yang diterapkan sekolah dalam menanamkan kedisiplinan meliputi peraturan tata tertib, konsisten dan hukuman. Berdasarkan observasi dan wawancara, nampak jelas adanya perubahan dari sebelum dan sesudah adanya pembacaan Barzanji. Pembacaan Barzanji dilaksanakan sesuai dengan jadwal yang sudah terstruktur. Kondisi ini tidak lepas dari dukungan komitmen setiap guru yang bertugas mendisiplinkan siswa. Hasil penelitian dapat disimpulkan bahwa keefektifan pembacaan Barzanji terhadap kedisiplinan siswa SMK Ganesha yakni untuk disiplin waktu, disiplin belajar dan disiplin dalam bersikap. Tidak hanya itu saja, karena siswa dalam setiap harinya pembacaan Barzanji merupakan pengajian bathin untuk menumbuhkan karakteristik anak menjadi siswa yang religius, emosional dan spiritual. Ketika memasuki kelas siswa menjadi pribadi yang tenang, rileks dan sejuk. Berbeda dengan siswa-siswa sebelum pembacaan Barzanji diadakan, ketika memasuki kelas kemudian menunggu bel masuk berbunyi siswa banyak bercanda dengan temannya yang mengakibatkan kericuhan dalam kelas. Kata Kunci: Pembacaan Barzanji, Kedisiplinan Siswa